ChemInform Abstract: Exploring the Borders of the Zintl‐Klemm Concept: On the Isopunctual Phases Eu5+xMg18‐xGe13 (x = 0.1) and Eu8Mg16Ge12. Issue 3 (22nd January 2013) - Slabon, Adam; Cuervo‐Reyes, Eduardo; Kubata, Christof; Mensing, Christian; Nesper, Reinhard
Abstract Eu5.1Mg17.9Ge13 (I) and Eu8Mg16Ge12 (II) are prepared by solid state reaction of the elements (Nb ampules, 890—1020 °C, 48 h—16 d).